2000
DOI: 10.1159/000015626
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific expression of an evolutionarily conserved male regulatory gene, <i>DMRT1</i>, in birds

Abstract: Based on its Z-sex-chromosomal location and its structural homology to male sexual regulatory factors in humans (DMRT1 and DMRT2), Drosophila (Dsx), and Caenorhabditis elegans (Mab-3), chicken DMRT1 is an excellent candidate for a testis-determining factor in birds. The data we present provide further strong support for this hypothesis. By whole mount in situ hybridization chicken DMRT1 is expressed at higher levels in the male than in the female genital ridges during early stages of embryogenesis. Its express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 27 publications
1
50
1
Order By: Relevance
“…The role of Dmrt1 in sex determination and differentiation of vertebrates has been studied in several species (Nanda et al 1999, Raymond et al 1999a,b, Kettlewell et al 2000, Marchand et al 2000, Shan et al 2000a, Smith et al 2003. In mice, humans, chicken, and turtles, Dmrt1 expression was found to be sexually dimorphic and restricted to the testis (Raymond et al 1999a,b, Kettlewell et al 2000, Shan et al 2000a, Smith et al 2003.…”
Section: Regulatory Action Of Estrogen On Dmrt1s Foxl2 and Cyp19s Imentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Dmrt1 in sex determination and differentiation of vertebrates has been studied in several species (Nanda et al 1999, Raymond et al 1999a,b, Kettlewell et al 2000, Marchand et al 2000, Shan et al 2000a, Smith et al 2003. In mice, humans, chicken, and turtles, Dmrt1 expression was found to be sexually dimorphic and restricted to the testis (Raymond et al 1999a,b, Kettlewell et al 2000, Shan et al 2000a, Smith et al 2003.…”
Section: Regulatory Action Of Estrogen On Dmrt1s Foxl2 and Cyp19s Imentioning
confidence: 99%
“…Mutation of Dmrt1 led to failure in producing differentiated testes resulting in germ cell death indicating that Dmrt1 is a prerequisite for testis differentiation in postnatal mouse . Also, a number of reports have demonstrated the essential roles of Dmrt1 in sex determination and differentiation in birds and reptiles (Nanda et al 1999, Shan et al 2000a, Torres et al 2002, Smith et al 2003. In fish, Dmrt1 was found to be expressed exclusively during the early stages of male gonad differentiation, but not in the female gonad in Nile tilapia (Guan et al 2000) and rainbow trout (Marchand et al 2000).…”
Section: Introductionmentioning
confidence: 97%
“…Pask et al, 2003;Raymond et al, 1999;Smith et al, 1999), birds (Nanda et al, 1999;Shan et al, 2000;Shetty et al, 2002;Smith et al, 1999), reptiles (Kettlewell et al, 2000;Smith et al, 1999) and fish (Brunner et al, 2001;Huang et al, 2005;Marchand et al, 2000). In each case except the mouse, DMRT1 is expressed at a higher level in potential male genital ridge than in potential female genital ridge before gonad differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…DMRT1 encodes a zinc finger-like transcription factor, and is structurally related to genes that have a male role in animals as distant as flies (Drosophila) and worms (Caenorhabditis elegans) (Raymond et al 1998). We and others have found that DMRT1 has a conserved male upregulated expression pattern in reptile, bird and mouse embryos (Raymond et al 1999;Smith et al 1999;Shan et al 2000). In the Chicken embryo, DMRT1 is expressed specifically in the urogenital system of both males (ZZ) and females (ZW), but is more highly expressed in males.…”
Section: The Dmrt1 Gene and Testis Developmentmentioning
confidence: 99%